A panel regression analysis of corporate governance mechanism and financial performance of listed cement industries in Nigeria - Olayinka, Aminu Abdulrahim; Kaka, Emmanuel John (Goodwood Publishing, 2025)
Purpose: Inquire into the significant correlation allying corporate governance mechanisms (CGMs) with financial performance (FP) of the prominent quoted cement firms in Nigeria. Methodology/approach: The study use panel data statistical modelling to investigate the time-dependent effects across different firms. The data analysis is based on a purely numerical dataset obtained through desk research, which was then scrutinized using the STATA 14.0 software package along with suitable statistical and econometric tools. Results/findings: The findings indicate a positive correlation between board structures and the FP of the selected cement companies in Nigeria. While the size of the board does not significantly influence performance, the presence of independent directors on the board positively affects financial performance. Conversely, there is a negative correlation between directors' compensation and the financial performance of these firms, suggesting that an increase in directors' compensation may lead to a decline in financial FP. Conclusion: The study concludes that there is a positive relationship between board structures and the financial performance, though board size is not a critical factor but the presence of independent directors on the board positively impacts financial performance. Limitations: The analysis is confined to five years Annual report and financial statements of three major firms in the Nigerian cement industry, covering a period from 2019 to 2023 using Panel-Corrected Standard Errors Regression model. Contribution: This comprehensive study evaluates the current state of corporate governance practices (CGPs) in Nigeria, aiming to identify improvements for CG policies.